Women Empowerment in Water Governance in Polder Zone in Bangladesh - Sarker, Mou Rani; Singaraju, Niyati; Batas, Mary Ann; Mondal, Manoranjan K.; Das, Mahanam; Puskur, Ranjitha; Yadav, Sudhir (2023)
The polders in coastal zones of Bangladesh are vulnerable to climate risks resulting in low agricultural productivity and low incomes for the communities dependent on agriculture-based livelihoods in these regions. Bangladesh adopted a participatory approach to water governance in the 1980s to improve the equitable and sustainable use of water resources. With men migrating away for better income opportunities, women are more involved in agricultural production and dependent on water resources. However, there is limited evidence on the implications of participatory water management on women’s empowerment outcomes – whether it results in improved participation and agency of women in farm production and control over farm incomes.